Pharmaceutical innovation: The gap between knowledge, attitude, and perceptions among pharmacists and final-year pharmacy students - Mohanad Odeh, Rami Amer, Abdel Qader Al Bawab, Mary-Carmel Kearney, Karem H. Alzoubi (Journal of Applied Pharmaceutical Science, 2022)
Recently, there has been an increasing interest in innovative business development. Nevertheless, in the pharmacy practice field, there seems to be a gap in perceptions, attitudes, and knowledge about innovation between practicing pharmacists and academia. This study explores this gap and aspects of pharmaceutical innovation in Jordan comparing pharmacists and last-year pharmacy students. A validated (r2 = 0.74) and reliable (Pearson’s r = 0.88) online questionnaire was designed to assess and compare knowledge, attitude, and perceptions about pharmaceutical innovation. A total of 397 participants (215 pharmacy students and 182 pharmaceutical professionals) responded. Compared with 50% of the pharmacists, only 32.1% of the students claimed that they knew the differences between pharmaceutical innovation, discovery, invention, and entrepreneurship [x2 (2) = 14.238, p = 0.001; Cramer’s V = 0.189]. Pharmacists demonstrated a higher level of trust in the innovative website design for their institution compared with students (25.3% vs. 16.3%, p < 0.001, Cramer’s V = 0.327). However, 60% of the students did not know the innovative design standards for websites, while the corresponding percentage was 37% for the pharmacists (p < 0.001; Cramer’s V = 0.327). The majority of the students were interested in pharmaceutical innovation (81.9%). Unfortunately, 76.3% never studied about innovation in their pharmacy curricula. Similarly, most pharmacists (76.4%) considered adopting innovation, but only 30% had a concrete plan. For the field where pharmacists aim to innovate in the next 5 years, new pharmaceutical services were the dominant field (34.6%). Despite a positive attitude and perception, pharmacists and pharmacy students expressed poor knowledge about innovation. Policies to enhance awareness about innovation and professional educational tools should be implemented.
Keywords: Innovation, entrepreneurship, knowledge, attitude, perception, pharmacists, pharmacy students